Tempo de trabalho e tempo de não trabalho dos bancários do Banco do Brasil e Caixa Econômica Federal de São Luís do Maranhão - Mendonça, Claudio Anselmo de Souza (2015)
In this thesis I present an analysis of the working time and non-working time of the bank employees of public banks of Sâo Luís, starting from an initial understanding of the working time of workers in general, along the history of capitalism has never left having certain primacy in struggles, including having at various times a more predominant role than the wage struggle. So based on an analysis of the totality and the contradiction, we understand that reflect on this issue in the context of actual capitalism, and having bank employees as category, is to reflect on financialization and the role of banks, beyond its structuring as national financial system in Brazil . We also sought to analyze the impacts of productive neoliberal restructuring, placing the workforce in this context, reaffirming the ontological role of work, however looking for dialogue with the various authors that question this issue, are denying the role of work as a mediator in the current context, is reaffirming, with new dimensions and categories. We start from the analysis of the bank employees category, locating them as working class, and thus demonstrating the futility of the dual theses on the job. This understanding of the role of the bank employees inside the dialectic of the class struggle allowed us to reflect on the particular struggles of this category to obtain 6 hours special working day and how this working hours is attacked in the present day via an ostensible ideological control, with an advanced process of intensification of precarization its activities. Finally, reflecting on this framework, we reaffirm that there is no emancipatory sense of the non-working time within an abstract work time and fetishized, that is, under capitalism, at most this non-working time takes on a character of relative autonomy , thus proving the thesis of the impossibility of effectiveness of free time without a break from the capital.